The effectiveness of compound exercises at specific distances in developing the explosive ability and the accuracy of some types of shooting with basketball for players of ages below 18 years old - Jsim, Layth Basim; Saleh, Hasim Abd Aljabar; Sachit, Hussein Mnaty (International Journal of Psychosocial Rehabilitation, 2020)
The research problem centered and based on the researcher's previous experience as a player in the Iraqi Premier League with basketball and his follow-up to the Iraqi Youth League matches and his field presence with players under the age of 18 years, it was found that most of the physical abilities, especially the explosive ability of the two men, suffer from a lack of training during the training units, which reflected negatively at the required level For this ability, as this ability is very important for a basketball player in terms of the nature of its use in jumping while performing the jump shot. The researcher also noted that some types of correction do not rise to the required level despite its importance in the match through the number of points that the team gets if recorded during the match which made the researcher interested in this problem by preparing exercises in a modern way to know their impact on the physical and skillful side of basketball players by preparing complex exercises with specific distances in the development of explosive ability and accuracy of some types of shooting for basketball players of ages below 18Year. The aim of the research is to: To prepare complex exercises with specific distances in the development of explosive ability and accuracy of some types of shooting for basketball players under 18 years of age and learning about the effect of compound exercises with specific distances in developing the explosive ability of players under 18 years of age with basketball. And to identify the effect of compound exercises with specific distances on developing the accuracy of some types of shooting for basketball players under 18 years old. And the researcher used the experimental method design (equal groups) to the nature of the problem and its suitability. As for the research community, it is identified with basketball players in the National Center for Sports Talent Development in Diyala Governorate, whose ages range from (16-18) years and whose number is (17) players for the 2019-2020 training season. The research sample was selected in a random, irregular method (the lottery) of (12) players for the training season (2019-2020) and (5) players for the exploratory experiment, and the original research sample was divided into two equal groups (control- experimental) and by (6) players per group. The exercises were applied for a period of (8) weeks in the special preparation stage to develop the explosive ability and accuracy of some types of aiming for the players. Among the most important conclusions reached by the researchers is that the compound exercises with specific distances prepared by the researcher helped in developing the explosive ability of the two legs and the accuracy of some types of aiming.